2014
DOI: 10.1177/0883073814535491
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Aquatic Therapy on Motor Function and Enjoyment in Children Diagnosed With Cerebral Palsy of Various Motor Severities

Abstract: This study investigates the effects of pediatric aquatic therapy on motor function, enjoyment, activities of daily living, and health-related quality of life for children with spastic cerebral palsy of various motor severities. Children with spastic cerebral palsy were assigned to a pediatric aquatic therapy group (n = 11; mean age = 85.0 ± 33.1 months; male : female = 4 : 7) or a control group (n = 13; mean age = 87.6 ± 34.0 months; male : female = 9 : 4). The statistic results indicate that the pediatric aqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 33 publications
3
54
0
4
Order By: Relevance
“…It has been observed that the growth was more than GMFM-88 (level II evidence) in children with level 2 GMFCS [2]. Most studies suggest that hydrotherapy exercises are useful and effective in children with GM-FCS levels 1 to 3.…”
Section: Application Of Hydrotherapy Methods According To the Gmfcs Lmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been observed that the growth was more than GMFM-88 (level II evidence) in children with level 2 GMFCS [2]. Most studies suggest that hydrotherapy exercises are useful and effective in children with GM-FCS levels 1 to 3.…”
Section: Application Of Hydrotherapy Methods According To the Gmfcs Lmentioning
confidence: 99%
“…In the hydrotherapy program with Halliwick approach, it was indicated that the water temperature should be kept between 33 and 36°C [2]. It was also noted that in water aerobics exercises, water temperature should be between 31 to 32°C [7].…”
Section: Environmental Factors Suitable For Implementationmentioning
confidence: 99%
See 3 more Smart Citations